2021
DOI: 10.1088/1742-6596/1892/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

Distinct optical response of colloidal gold-cinnamon nanocomposites: Role of pH sensitization

Abstract: Nanocomposites (NCPs) with excellent physical, chemical and optical properties have been broadly used for commercial products and industrial applications. Based on these features of the NCPs, we prepared colloidal gold (Au) and organic cinnamon (Cin) NCPs by laser irradiated Au and Cin targets separately immersed in glass container fulfilled with different pH solutions (5.0 to 8.0). A Q-switched pulse laser ablation in liquid (PLAL) technique was employed to customize morphology, structural and optical charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Then, we used COVID-19 Radiography Database (COVID-Dataset) with three classes (COVID, Pneumonia, and Normal). Next, we applied our enhancement technique to the COVID-Dataset [17][18][19]. Finally, the enhanced dataset images are trained with our CNN to generate a model to classify the images into COVID, Pneumonia, or Normal.…”
Section: Methodsmentioning
confidence: 99%
“…Then, we used COVID-19 Radiography Database (COVID-Dataset) with three classes (COVID, Pneumonia, and Normal). Next, we applied our enhancement technique to the COVID-Dataset [17][18][19]. Finally, the enhanced dataset images are trained with our CNN to generate a model to classify the images into COVID, Pneumonia, or Normal.…”
Section: Methodsmentioning
confidence: 99%
“…They were able to attain an 81% rate of correct categorization. In their research, Ayan and Unver [24][25][26] shown how data augmentation may boost the accuracy of deep learning-based melanoma categorization. They took 1000 original photos of varying sizes from the famous ISIC dataset, splitting them in half to create sets of 500 images representing malignant and benign tumors.…”
Section: Related Workmentioning
confidence: 99%
“…In contrast, the value of the correlation coefficient is close to 0, in encrypted images. Therefore, one of the most important objectives of effective encryption algorithms is to obtain an encrypted image with the lowest possible correlation [43][44][45][46]. Fig.…”
Section: B Correlation Coefficientmentioning
confidence: 99%